The Impact of Graded Levels of Talinum fruticosum Leaf Meal on Reproductive Indices and Organs of Rabbit Bucks (American Journal of Aquaculture and Animal Science, 2025)
The aim of this study was to investigate the influence of Talinum fruticosum leaf meal (TFLM) supplement in the diet of 24 New Zealand rabbit bucks (crosses) on their semen parameters, reproductive hormones production and selected internal organs. TFLM was incorporated into their diets at 0, 5, 10, and 15%, representing treatments (T) 1 (Control), 2, 3, and 4 respectively. After 8 weeks of exposure to the diets, data were collected, analysed and the results showed that TFLM produced no effect on semen volume, concentration, normal morphology, mortality, livability and colour, but resulted in significant rise (p